Mechanisms of the formation of education workers’ professional competence in the field of intellectual property - Fesenko , Nataliya; Ruban , Nataliia (Theory and Practice of Public Administration, 2019)
Against the background of the global trends in the development of post-industrial countries, the article highlights the issue of competence of education professionals in the field of intellectual property protection. The analysis of the current state of affairs confirms a complete lack of professional competence regarding the registration and protection of intellectual property rights among those working in the system of general secondary education and its partial formation among the vast majority of higher education teaching professionals. The most effective solution to this problem is massive training of educators in the field of intellectual property protection and their further professional growth in this area. Educators are imaginative individuals who create innovative developments to achieve the goals of the teaching and learning process. At the same time, they are not able to provide legal protection for their own creative works, evaluate the possibility of their commercialization, and take measures in case of unfair competition. Such a distinct lack of professionalism among the intelligentsia in Ukraine in matters of intellectual property protection is conditioned by the fact that traditionally in the system of Ukrainian education, including higher education, there has been no special training in the fundamentals of intellectual property within compulsory courses on the basis of the relevant conception. The absence of legally defined intellectual property of educators and education institutions leads to the possibility of freely dealing with their intellectual property rights. In order to solve the problem of innovative products right protection, it is necessary to develop competences in the area of copyright enforcement among academic personnel and introduce a systematic study of the elements of intellectual property protection by using information and communication technology. Much attention is paid to the theoretical and methodological bases of professional training of pedagogical workers, with special emphasis being placed on the relevant experience in developed countries of the world. The intensification of the processes of diversification of postgraduate pedagogical education has led to the search for new modern methods and forms of advanced training, one of which is the transfer of pedagogical and managerial technologies. Unlike the classical advanced training, technology transfer involves the provision of the right to use intellectual property objects, transfer of technological documentation, information exchange, and the involvement of skilled workers with specialized knowledge. As a result of advanced training in the field of intellectual property, educators will be able to provide legal protection for their original works of authorship, evaluate the possibility of their commercialization, take measures to prevent unfair competition, educate socially responsible students capable of creating, using and protecting intellectual property, inspire students to launch startups based on the products of their intellectual work, etc.